A Case Report: Multidrug-Resistant Tuberculosis in A 53-Year-Old Patient - Mustofa, Syazili; Ananta, Yoga; Ginting, Bisart; Septiani, Linda; Busman, Hendri (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
A 53-year-old man with multidrug-resistant tuberculosis (MDR-TB) presented with clinical symptoms such as cough with yellow-white sputum for a month, shortness of breath, fever, night sweats, and weight loss. After completing six months of TB treatment in 2010, he developed MDR-TB, proven by resistance to rifampicin. Initial diagnosis by chest X-ray showed signs of pulmonary TB and right pleural effusion, while the sputum test confirmed Mycobacterium tuberculosis with moderate bacterial load. Laboratory results showed anemia, leukocytosis, and hypoalbuminemia. The patient's therapy included a combination of bedaquiline, levofloxacin, linezolid, clofazimine, cycloserine, and vitamin B6, along with additional treatments such as antibiotics, symptomatic therapy, and nutritional support. The medical team conducted regular monitoring and consultation with pulmonary, psychiatry, and nutrition specialists to ensure treatment compliance. This case highlights the challenges in managing MDR-TB, especially in patients with a history of TB. Early detection of drug resistance and prompt implementation of appropriate therapy are essential to improve treatment outcomes and prevent further spread. This report emphasizes the need for a multidisciplinary approach and close monitoring in the management of MDR-TB.